Prevalence and influencing factors of frailty in older patients with diabetes in China: a system review and meta-analysis - Liu, Jian; Cao, Yanjun; Wang, Qingjie; Wang, Zhiwei; Luan, Xiaorong (Frontiers in Medicine, 2023)
Background and aims To systematically evaluate the relevant literature to explore the prevalence and influencing factors of frailty in older patients with diabetes in China. Methods Cochrane Library, PubMed, Embase, Medline, CINAHL, Scopus, Proquest Central, Web of Science, SinoMed, CNKI, VIP and Wan fang Databases were searched to collect Chinese and English literatures about frailty in older diabetic patients. RevMan 5.4 software was used to extract data for systematic review. Results Seventeen studies involving 23,070 older patients with diabetes were included. The results showed that the prevalence of frailty in older Chinese diabetic patients was 30%. The main influencing factors were HbA1c level, number of complications, age, depression, exercise, and nutritional status. Conclusion The prevalence of frailty in Chinese elderly diabetic patients is high and there are many influencing factors. However, the quality of relevant literature is general and the number is limited, so high-quality prospective studies should be carried out in the future to further verify the conclusions.